Electrodeposited, Ni-based, non-noble metal coatings as cathodes for hydrogen evolution in chlor-alkali electrolysis - Borka M. Jović; Nedeljko V. Krstajić (Zaštita Materijala)
The hydrogen evolution reaction (HER) has been investigated on two types of electrodeposited, Nibased, non-noble metal coatings: composite coatings with inclusion of MoO2 particles and electrodeposited NiSn alloy coatings, in order to find suitable replacement for noble metal coatings (commercial De Nora's Ni-RuO2 electrode (DN)), as cathodes for industrial application in the zero-gap membrane cell for chlor-alkali electrolysis. Some samples of both types of cathodes showed better catalytic activity for the HER than the DN electrode under the conditions of industrial applications: 32 mass % NaOH at 90°C and j = -0.3 A cm-2. Since lower overvoltage for the HER is not the only criteria for successful application in industrial electrolysis, service life test (SLT), simulating long time operation of cathodes, has been applied for both types of cathodes. It has also been shown that certain samples of both types of cathodes could be promising replacement for the commercial DN electrode since they showed better performance during the SLT.